Swine manure treatment by anaerobic membrane bioreactor with carbon, nitrogen and phosphorus recovery - Bu, Fan (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
Swine manure wastewater was treated in an anaerobic membrane bioreactor (AnMBR) that combined a continuous stirred tank reactor (CSTR) and a hollow-fiber ultrafiltration membrane, and the feasibility of ammonia and phosphorus recovery in the permeate was investigated. The AnMBR system was operated steadily with a high mixed liquor suspended solids (MLSS) concentration of 32.32 ± 6.24 g/L for 120 days, achieving an average methane yield of 280 mL/gVSadded and total chemical oxygen demand removal efficiency of 96%. The methane yield of the AnMBR is 83% higher than that of the single CSTR. The membrane fouling mechanism was examined, and MLSS and the polysaccharide contents of the extracellular polymeric substances were found to be the direct causes of membrane fouling. The effects of the permeation/relaxation rate and physical, chemical cleaning on membrane fouling were assessed for membrane fouling control, and results showed that a decrease in the permeation/relaxation rate together with chemical cleaning effectively reduced membrane fouling. In addition, a crystallization process was used for ammonia and phosphorus recovery from the permeate, and pH 9 was the optimal condition for struvite formation. The study has an instructive significance to the industrial applications of AnMBRs in treating high strength wastewater with nutrient recovery